Tipologi reka bentuk masjid tradisional di Indonesia - Nangkula Utaberta,; Kamarul Afizi Kosman,; Azimin Samsul Mohd Tazilan, (Universiti Kebangsaan Malaysia, 2009)
The main objective of this paper is to identify and explain the development of form and structure of traditional mosques in Indonesia. This research is important in order to understand the morphology and tectonical aspect of mosques design in Nusantara as a whole. The discussion will be divided into two main parts which is the special character of traditional mosques in Indonesia and important elementsof the mosque architecture in Indonesia. It is expected from this short paper we can get brief picture of mosque architecture development in Indoenesia as a materials to develop future thought and mosque design in Nusantara